PSI-33 Distribution and localization of porcine calcium sensing receptor (pCaSR) in different tissues in weaned piglets. (7th December 2018) - Zhao, X; Schindell, B; Li, W; Ni, L; Liu, S; Gong, J; Nyachoti, C; O, K; Yang, C
Abstract: Taste receptors including calcium sensing receptor (CaSR) are expressed in various animal tissues, which play important roles in nutrient sensing and regulate the physiology, growth and development of animals. However, molecular distribution and localization of pig CaSR (pCaSR) in different tissues and along the longitudinal axis of the intestine in pigs are still unknown. In the present study, we investigated the molecular distribution and localization of pCaSR in different tissues including intestinal segments of weaned piglets. Six male pigs ([Yorkshine-Landrace] - Duroc, weaned at 21 ± 2 d) at the age of 28 d were anesthetized by an intramuscular injection of ketamine:xylazine and euthanized by intravenous injection of sodium pentobarbital. Different tissues including intestinal segments were collected. The pCaSR mRNA abundance and protein localization were measured by real-time PCR and immunohistochemistry, respectively. The mRNA and protein of pCaSR were detected in the kidney, lung, liver, stomach, duodenum, jejunum, ileum and colon. The pCaSR mRNA was much higher (5 to180 times) in the kidney when compared with other tissues (P < 0.05). The ileum had higher (4 to18 times) pCaSR mRNA abundance than the stomach, duodenum, jejunum and colon (P < 0.05). However, there was no significant difference in pCaSR mRNA abundance observed among the stomach, duodenum and jejunum (P > 0.05). The pCaSR protein was mostly located in the epithelia of the stomach, duodenum, jejunum, ileum and colon. These results demonstrate that pCaSR is widely expressed in different tissues including intestinal segments in weaned piglets and that the kidney and ileum have higher expression levels of pCaSR. The functional characterization of pCaSR gene and its ligands requires further investigation.